Microcapsule as well as preparation method and application thereof
By designing microcapsules with elastic modulus and thickness of the capsule wall and adding active components to the capsule wall, the problem of insufficient binding strength between microcapsules and asphalt is solved, and the effect of self-healing of asphalt pavement and reducing the release of volatile organic matter is achieved.
Patent Information
- Application Number
- CN202311125654.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-09-01
AI Technical Summary
In the prior art, the binding strength between microcapsules and asphalt is insufficient, which makes it difficult for microcapsules to rupture, affecting the self-repair efficiency. At the same time, the unorganized release of volatile organic matter during the asphalt pavement construction process, polluting the environment.
A new microcapsule is designed with the elastic modulus and thickness of the capsule wall to meet a specific formula relationship, ensuring good binding strength with asphalt, and adding active components, such as aromatic hydrocarbon components or inhibitors to the capsule wall to increase the chance of rupture and prolong the action time.
The effective cracking and repair agent release of microcapsules in asphalt pavement is achieved, the road surface self-repair efficiency is improved, and the volatile organic matter released unorganized during asphalt construction is reduced, thereby protecting the environment.
Smart Images

Figure CN119552518A_ABST
Abstract
Description
Technical Field
[0003] The present invention relates to the technical field of microcapsule materials, and in particular to a microcapsule and a preparation method and application thereof, and more particularly to a microcapsule and a preparation method thereof and application of the microcapsule in road asphalt. Background Art
[0004] During the use of asphalt pavement, due to the influence of vehicle loads and environmental factors, micro cracks and local damage are very likely to occur inside. If not controlled in time, the micro cracks will expand and crack under the action of external loads, leading to the formation of macro cracks. Water seepage at the cracks will further aggravate the damage to the pavement structure, making it impossible for the road to reach its designed service life. Since micro cracks in asphalt pavement are often generated inside, it is very difficult to detect such micro damage in time, and it is almost impossible to carry out manual repairs, so that it is difficult to repair the initial cracks. In severe cases, macro cracks will be caused and lead to structural fractures. The current repair method is to take remedial measures only after obvious cracks appear on the pavement. Although this repair can solve the existing problems, it will inevitably have a certain impact on traffic, resulting in multiple losses of manpower and material resources.
[0005] The repair agent is encapsulated in microcapsules through microcapsule technology, and the automatic repair of pavement cracks can be achieved after adding asphalt. When microcracks appear in asphalt due to aging or load, the microcapsules at the crack path will rupture due to the expansion of tip stress; the repair agent is released from the microcapsule wall material, and under the impetus of capillary action, it flows along the microcracks and penetrates and diffuses to both sides of the microcracks, making the microcracks gradually disappear, and finally achieving the effect of self-repair of asphalt. During the use of asphalt pavement, the microcapsules must have sufficient strength to avoid rupture during the mixing of asphalt mixtures. However, if the strength of the microcapsules is too high, when microcracks appear on the asphalt pavement, the cracks are likely to bypass the microcapsules and expand forward, making it difficult for the microcapsules to rupture and unable to play their repair role.
[0006] Chinese patent application CN104231642A discloses a self-repairing microcapsule for asphalt cracks containing a regeneration agent and a preparation method thereof. The method uses polyurea formaldehyde resin as the wall material and the asphalt regeneration agent as the core material to prepare the self-repairing microcapsules for asphalt cracks, which can enhance the self-repairing ability of asphalt pavement to a certain extent. However, the microcapsules are not tightly combined with the asphalt, and the microcapsules are prone to being difficult to break, which affects the self-repairing efficiency of the microcapsules.
[0007] In summary, the existing technology does not take into account the bonding strength between microcapsules and asphalt, but simply adds microcapsules into asphalt. The two cannot be effectively integrated, making it easy for the microcapsules to separate from the asphalt, further exacerbating the occurrence of the microcapsule rupture difficulty phenomenon.
[0008] In addition, as the main type of highway, asphalt pavement still uses the traditional hot-mix hot-paving process in its pavement construction. During the construction process, the asphalt will come into contact with oxygen in the air and react: on the one hand, condensation reaction will occur to produce polycyclic aromatic hydrocarbons with larger molecular weight, which will further condense into gums and asphaltene; on the other hand, asphalt molecules will crack under heat conditions to produce compounds with smaller molecular weight. These small molecular compounds will evaporate to form asphalt fumes, which will seriously damage the ecological balance, pollute the surrounding environment and harm human health.
[0009] Given that asphalt pavement releases volatile organic compounds (VOCs) in an unorganized manner during the paving process, it is difficult to collect and control the entire process. It is an urgent issue that needs to be addressed at present to explore how to reduce asphalt fume release at the source, achieve clean asphalt pavement construction, and ensure the harmonious development of the transportation industry and the social economy. Summary of the invention
[0010] The purpose of the present invention is to overcome the problem in the prior art that the microcapsule material cannot be effectively fused after being added to asphalt, so that the microcapsule is easily separated from the asphalt, and to provide a new microcapsule and its preparation method and application. The microcapsule of the present invention not only has high strength, meets the requirements of road use, but also has good bonding strength with asphalt.
[0011] In order to achieve the above object, the present invention provides a microcapsule on one hand, the microcapsule comprises a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0012] Y=0.42X 2 -0.92X+T
[0013] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0014] The elastic modulus of the microcapsule is obtained by testing the mechanical properties of the microcapsule using a nanoindenter, and the thickness of the capsule wall is obtained by testing the frozen sections of the microcapsule using a scanning electron microscope.
[0015] Preferably, based on the total weight of the microcapsule, the content of the capsule core is 27-53 wt.%, and the content of the capsule wall is 47-73 wt.%.
[0016] Preferably, the active component is a repairing agent for self-repair of pavement cracks and / or an inhibitor for inhibiting the release of asphalt smoke.
[0017] Preferably, the repairing agent for self-repair of pavement cracks is an aromatics-rich component.
[0018] Preferably, the aromatics-rich component is selected from at least one of catalytic cracking slurry, oil extracted from a four-line reduction reactor, furfural extracted oil and waste lubricating oil.
[0019] Preferably, the aromatic content of the aromatic-rich component is 45-65 wt.%.
[0020] Preferably, the inhibitor for inhibiting the release of asphalt fume is at least one of aldehyde compounds, ketone compounds, alcohol compounds, phenol compounds and ester compounds.
[0021] Preferably, the aldehyde compound is selected from aliphatic aldehydes having carbon atoms greater than or equal to 7 and aromatic aldehydes having carbon atoms greater than or equal to 6, more preferably at least one of p-tolualdehyde, decanal, o-carboxybenzaldehyde, p-isopropylbenzaldehyde, cinnamaldehyde, p-hydroxybenzaldehyde, p-methoxybenzaldehyde, 2-methyl-3-(3,4-methylene-dioxyphenyl)propanal, 3,4-methylenedioxybenzaldehyde, 3-(4-isopropylphenyl)-2-methylpropanal, ethyl vanillin, phenylacetaldehyde, anisaldehyde, nonadiene-2,6-aldehyde, 2,6-dimethyl-2,6-octadienal, vanillin, citronellal, neral, hydroxymethylpentylcyclohexene acetal, p-diethylaminobenzaldehyde and undecenal.
[0022] Preferably, the ketone compound is selected from aliphatic ketones having a carbon number greater than or equal to 8 and aromatic ketones having a carbon number greater than or equal to 8, and more preferably is at least one of 6-methyl-3,5-heptadien-2-one, 2-undecanone, acetophenone, ionone, irone, methylionone, damascenone and dihydrodamascenone.
[0023] Preferably, the alcohol compound is an alcohol having more than 6 carbon atoms, more preferably at least one of cinnamyl alcohol, menthol, cis-3,7-dimethyl-2,6-octadienol, citronellol, geraniol, myrcenol, 2,6,10-trimethyl-2,6,10-dodecatrien-12-ol, lavandulol, benzyl alcohol, 2-phenylethanol, dihydromyrcenol, tetrahydrogeraniol and nerolidol.
[0024] Preferably, the phenolic compound is a phenol having 6 or more carbon atoms, more preferably at least one of thymol, ethyl maltol, methyl maltol, 3-propenyl-6-ethoxyphenol and isoeugenol.
[0025] Preferably, the ester compound is an ester having a carbon number greater than 7, more preferably at least one of methyl salicylate, methyl cinnamate, ethyl cinnamate, ethyl phenylacetate, methyl phenylacetate, geranyl phenylacetate, phenylethyl phenylacetate, isoamyl phenylacetate, benzyl salicylate, p-methylbenzyl acetate, benzyl acetate, isobutyl benzoate, isoamyl salicylate, benzyl cinnamate, phenylethyl cinnamate, linalyl formate, linalyl acetate, linalyl isobutyrate, menthyl acetate, pine acetate and bornyl acetate.
[0026] Preferably, the thickness of the capsule wall is 0.5-5 μm.
[0027] Preferably, the bladder wall comprises an inner layer and an outer layer, the inner layer is resin, and the outer layer is rubber material.
[0028] Preferably, the mass ratio of the inner layer to the outer layer is 2.4-5:1.
[0029] Preferably, the resin is at least one of melamine resin, urea-formaldehyde resin and polymethyl methacrylate, preferably melamine resin.
[0030] Preferably, the rubber material is at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
[0031] Preferably, the size of the microcapsule is 50 μm or less, preferably 20 μm or less, and more preferably 3-15 μm.
[0032] A second aspect of the present invention provides a method for preparing microcapsules, the method comprising:
[0033] (1) mixing the active ingredient, emulsifier and water to form an oil-in-water emulsion;
[0034] (2) reacting the oil-in-water emulsion with a resin prepolymer, and then filtering, washing, and drying to obtain a pre-coated material;
[0035] (3) In the presence of a volatile solvent, the rubber material and the pre-coated material are mixed, and then the obtained mixture is mixed with water, and the temperature is raised until the volatile solvent evaporates to obtain microcapsules.
[0036] Preferably, in step (1), the mass ratio of the active component, the emulsifier and water is 1:(0.05-0.09):(6-9).
[0037] Preferably, in step (2), before the oil-in-water emulsion reacts with the resin prepolymer, the pH value of the oil-in-water emulsion is adjusted to below 5, preferably 2-4.
[0038] Preferably, in step (2), the resin prepolymer is a melamine resin prepolymer.
[0039] Preferably, the preparation method of the melamine resin prepolymer comprises: mixing and dissolving melamine and formaldehyde solution with water, adjusting the pH value to 7.5-9.5, and then placing in a constant temperature water bath at 60-90° C. and reacting for 0.5-3.5 hours under stirring.
[0040] Preferably, the concentration of the formaldehyde solution is 30-40 wt.%.
[0041] Preferably, the mass ratio of the melamine, the formaldehyde solution and the water is 1:(2-3):(8-10).
[0042] Preferably, in step (3), the mass ratio of the rubber material, the volatile solvent and water is 1:(10-20):(50-150).
[0043] Preferably, the active component is one or any combination of at least two or more of an aromatic hydrocarbon-rich component, an aldehyde compound, a ketone compound, an alcohol compound, a phenol compound and an ester compound.
[0044] Preferably, the rubber material is at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
[0045] Preferably, the emulsifier is selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, cetyltrimethylammonium chloride, cetyltrimethylammonium bromide, cetyldimethylhydroxyethylammonium chloride, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and hexadecane polyoxyethylene ether.
[0046] Preferably, the volatile solvent is selected from at least one of carbon tetrachloride, dichloromethane and trichloroethylene.
[0047] The third aspect of the present invention provides microcapsules prepared by the above method.
[0048] A fourth aspect of the present invention provides the use of the above-mentioned microcapsules in road asphalt.
[0049] According to the microcapsule of the present invention, the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy a specific functional relationship. In practical applications, the elastic modulus of the microcapsule can be controlled within a required parameter range by adjusting the thickness of the capsule wall.
[0050] In a more preferred embodiment, the active component in the capsule core is selected as a repair agent for self-repair of road cracks, and the capsule wall includes an inner layer and an outer layer, the inner layer is a resin, and the outer layer is a rubber material. The microcapsules of this preferred embodiment are particularly suitable for road asphalt. On the one hand, the microcapsules have a certain strength to meet the requirements of road use; on the other hand, the rubber material as the outer capsule wall can be effectively integrated with asphalt. The rubber material has good adhesion and forms a strong bond with the resin (especially melamine resin) as the inner capsule wall. When cracks appear on the asphalt pavement, the probability of material rupture can be effectively increased. The tearing of the outer capsule wall drives the tearing of the inner capsule wall, releasing the repair agent, and achieving the purpose of automatic repair. The two capsule wall materials can complement each other's advantages, thereby effectively improving the self-repair efficiency of road asphalt materials.
[0051] In another preferred embodiment, the active component in the capsule core is selected as an inhibitor for inhibiting the release of asphalt smoke, and the capsule wall includes an inner layer and an outer layer, the inner layer is a resin, and the outer layer is a rubber material. The microcapsule of this preferred embodiment is particularly suitable for road asphalt. The structure of the microcapsule can extend the action time of the active component, so that the road asphalt has a longer storage and service life. During the asphalt construction process, it can effectively reduce the emission of asphalt smoke and reduce pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is the SEM image of the microcapsules prepared in Example 1. DETAILED DESCRIPTION
[0053] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0054] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0055] The microcapsule of the present invention comprises a capsule core and a capsule wall, wherein the capsule core is wrapped in the capsule wall, the capsule core contains active components, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0056] Y=0.42X 2 -0.92X+T
[0057] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0058] The elastic modulus of the microcapsule is obtained by testing the mechanical properties of the microcapsule using a nanoindenter, and the thickness of the capsule wall is obtained by testing the frozen sections of the microcapsule using a scanning electron microscope.
[0059] In the microcapsule of the present invention, the thickness of the capsule wall can be 0.5-5 μm, specifically, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7 μm, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm or 5μm.
[0060] In some embodiments, the capsule wall has a thickness of 0.5-2 μm, preferably 0.5-1.5 μm. The capsule wall of the microcapsule of this embodiment is thinner, and the elastic modulus of the microcapsule is smaller, which is suitable for application scenarios requiring rapid release of the active component in the capsule core.
[0061] In other embodiments, the thickness of the capsule wall is 2-3 μm. The capsule wall of the microcapsule of this embodiment is moderate, and the elastic modulus of the microcapsule is moderate, which is suitable for application scenarios requiring the active component in the capsule core to be released at a moderate speed.
[0062] In other embodiments, the thickness of the capsule wall is 3-5 μm. The capsule wall of the microcapsule of this embodiment is thicker, the elastic modulus of the microcapsule is larger, and it is suitable for application scenarios where the active component in the capsule core needs to be released slowly.
[0063] In the microcapsule of the present invention, the size of the microcapsule may be less than 50 μm, preferably less than 20 μm, and more preferably 3-15 μm.
[0064] In the microcapsule of the present invention, based on the total weight of the microcapsule, the content of the capsule core can be 27-53wt.%, and the content of the capsule wall can be 47-73wt.%. In some embodiments, in the microcapsule, the content of the capsule core can be 40-53wt.%, and the content of the capsule wall can be 47-60wt.%; in other embodiments, in the microcapsule, the content of the capsule core can be 30-40wt.%, and the content of the capsule wall can be 60-70wt.%; in other embodiments, in the microcapsule, the content of the capsule core can be 27-30wt.%, and the content of the capsule wall can be 70-73wt.%.
[0065] In the microcapsules described in the present invention, the active components can be various conventional active components in sustained-release application scenarios. In some embodiments, the active component is a repairing agent for self-repair of pavement cracks and / or an inhibitor for inhibiting the release of asphalt fumes. When the active component in the microcapsule is a repairing agent for self-repair of pavement cracks, in the event of cracks in the asphalt pavement, the probability of material rupture can be effectively increased, and the tearing of the outer wall layer drives the tearing of the inner wall layer, releasing the repairing agent to achieve the purpose of automatic repair. When the active component in the microcapsule is an inhibitor for inhibiting the release of asphalt fumes, the structure of the microcapsule can extend the action time of the active component, so that the asphalt composition has a longer storage and service life. During the asphalt construction process, it can effectively reduce the emission of asphalt fumes and reduce pollution to the environment.
[0066] In the present invention, the repairing agent for self-repair of pavement cracks is preferably an aromatics-rich component. The aromatics-rich component refers to a material with an aromatics content of 40wt.% or more. As a specific material selection, the aromatics-rich component can be selected from at least one of catalytic cracking oil slurry, four-line extraction oil, furfural extraction oil and waste lubricating oil. In a preferred case, the aromatics content of the aromatics-rich component is 45-65wt.%, more preferably 50-60wt.%, and further preferably 52-56wt.%.
[0067] In the present invention, the inhibitor for inhibiting the release of asphalt smoke is preferably at least one of aldehyde compounds, ketone compounds, alcohol compounds, phenol compounds and ester compounds.
[0068] In the present invention, the aldehyde compound may be at least one of a fatty aldehyde having a carbon number greater than or equal to 7 and an aromatic aldehyde having a carbon number greater than or equal to 6. In a preferred case, the aldehyde compound is at least one of a fatty aldehyde of C7-C13 and an aromatic aldehyde of C6-C13. Specifically, the aldehyde compound is selected from at least one of p-methylbenzaldehyde, decanal, o-carboxybenzaldehyde, p-isopropylbenzaldehyde, cinnamaldehyde, p-hydroxybenzaldehyde, p-methoxybenzaldehyde, 2-methyl-3-(3,4-methylene-dioxyphenyl)propanal, 3,4-methylenedioxybenzaldehyde, 3-(4-isopropylphenyl)-2-methylpropanal, ethyl vanillin, phenylacetaldehyde, nonadiene-2,6-aldehyde, 2,6-dimethyl-2,6-octadienal, vanillin, citronellal, neral, hydroxymethylpentylcyclohexene acetal, p-diethylaminobenzaldehyde and undecenal.
[0069] In the present invention, the ketone compound may be at least one of an aliphatic ketone having a carbon number greater than or equal to 8 and an aromatic ketone having a carbon number greater than or equal to 8. Preferably, the ketone compound is at least one of an aliphatic ketone of C8-C11 and an aromatic ketone of C8-C14. Specifically, the ketone compound is selected from at least one of 6-methyl-3,5-heptadien-2-one, 2-undecanone, acetophenone, ionone, irone, methylionone, damascone and dihydrodamascone.
[0070] In the present invention, the alcohol compound is an alcohol having more than 6 carbon atoms, preferably an alcohol of C7-C15. Specifically, the alcohol compound is at least one of cinnamyl alcohol, menthol, cis-3,7-dimethyl-2,6-octadienol, citronellol, geraniol, myrcenol, 2,6,10-trimethyl-2,6,10-dodecatrien-12-ol, lavandulol, benzylenol, 2-phenylethanol, dihydromyrcenol, tetrahydrogeraniol and nerolidol.
[0071] In the present invention, the phenolic compound is a phenol having carbon atoms greater than or equal to 6, preferably a C6-C15 phenol. Specifically, the phenolic compound is at least one of thymol, ethyl maltol, methyl maltol, 3-propenyl-6-ethoxyphenol and isoeugenol.
[0072] In the present invention, the ester compound is an ester having a carbon number greater than 7, preferably an ester of C8-C17. Specifically, the ester compound is at least one of methyl salicylate, methyl cinnamate, ethyl cinnamate, ethyl phenylacetate, methyl phenylacetate, geranyl phenylacetate, phenylethyl phenylacetate, isoamyl phenylacetate, benzyl salicylate, p-methylbenzyl acetate, benzyl acetate, isobutyl benzoate, isoamyl salicylate, benzyl cinnamate, phenylethyl cinnamate, linalyl formate, linalyl acetate, linalyl isobutyrate, menthyl acetate, pine acetate and bornyl acetate.
[0073] In the microcapsules of the present invention, in a preferred case, the capsule wall includes an inner layer and an outer layer, the inner layer is a resin, and the outer layer is a rubber material. In this preferred case, the microcapsule material is particularly suitable for road asphalt. On the one hand, the microcapsules have a certain strength to meet the requirements of road use; on the other hand, the rubber material as the outer capsule wall can be effectively integrated with asphalt. The rubber material has good adhesion and forms a strong bond with the resin (especially melamine resin) as the inner capsule wall. When cracks appear on the asphalt road surface, the probability of material rupture can be effectively increased. The tearing of the outer capsule wall drives the tearing of the inner capsule wall, releasing the repair agent, and achieving the purpose of automatic repair.
[0074] Further preferably, the mass ratio of the inner layer to the outer layer is 2.4-5:1, for example, it can be 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5:1.
[0075] In the present invention, the content of the capsule core, the content of the capsule wall, and the mass of the inner layer and the outer layer of the capsule wall of the microcapsule are detected by the following method: the microcapsule is added to a volatile solvent (the volatile solvent can be selected from one or more of carbon tetrachloride, dichloromethane and trichloroethylene), and after fully dissolving and filtering, the first solid powder obtained is fully dried, and the difference between the mass of the first solid powder and the initial microcapsule is the mass of the capsule wall outer layer; the first solid powder obtained is further fully ground, added to toluene, and after fully dissolving and filtering, the second solid powder obtained is fully dried, and the difference between the mass of the first solid powder and the first solid powder is the mass of the capsule core; the mass of the inner layer of the capsule wall is the mass of the microcapsule minus the mass of the outer layer of the capsule wall and the mass of the capsule core.
[0076] In the present invention, the resin may be at least one of melamine resin, urea-formaldehyde resin and polymethyl methacrylate, and melamine resin is most preferred.
[0077] In the present invention, the rubber material may be at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
[0078] In some specific embodiments of the present invention, the microcapsule comprises a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0079] Y=0.42X 2 -0.92X+T
[0080] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0081] The thickness of the capsule wall is 0.5-5 μm. Based on the total weight of the microcapsule, the content of the capsule core can be 27-53 wt.%, and the content of the capsule wall can be 47-73 wt.%.
[0082] In some other specific embodiments of the present invention, the microcapsule comprises a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0083] Y=0.42X 2 -0.92X+T
[0084] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0085] The thickness of the capsule wall is 0.5-5 μm, and based on the total weight of the microcapsule, the content of the capsule core can be 27-53 wt.%, and the content of the capsule wall can be 47-73 wt.%;
[0086] The active component is a repairing agent for self-repair of pavement cracks and / or an inhibitor for inhibiting the release of asphalt smoke;
[0087] The bladder wall comprises an inner layer and an outer layer, the inner layer is made of resin, the outer layer is made of rubber material, and the mass ratio of the inner layer to the outer layer is 2.4-5:1.
[0088] In some other specific embodiments of the present invention, the microcapsule comprises a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0089] Y=0.42X 2 -0.92X+T
[0090] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0091] The thickness of the capsule wall is 0.5-5 μm, and based on the total weight of the microcapsule, the content of the capsule core can be 30-40 wt.%, and the content of the capsule wall can be 60-70 wt.%;
[0092] The active component is a repair agent (such as an aromatics-rich component) for self-repair of pavement cracks;
[0093] The bladder wall comprises an inner layer and an outer layer, the inner layer is made of melamine resin, the outer layer is made of rubber material, and the mass ratio of the inner layer to the outer layer is 2.4-5:1.
[0094] In some other specific embodiments of the present invention, the microcapsule comprises a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0095] Y=0.42X 2 -0.92X+T
[0096] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0097] The thickness of the capsule wall is 0.5-1.5 μm;
[0098] The active component is an inhibitor for inhibiting the release of asphalt smoke (such as aldehyde compounds, ketone compounds, alcohol compounds, phenolic compounds or ester compounds);
[0099] The bladder wall comprises an inner layer and an outer layer, the inner layer is melamine resin, and the outer layer is rubber material;
[0100] The mass ratio of the capsule core, the inner layer and the outer layer is 1:0.7-1:0.2-0.3.
[0101] In some other specific embodiments of the present invention, the microcapsule comprises a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0102] Y=0.42X 2 -0.92X+T
[0103] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0104] The thickness of the capsule wall is 2.1-3 μm;
[0105] The active component is an inhibitor for inhibiting the release of asphalt smoke (such as aldehyde compounds, ketone compounds, alcohol compounds, phenolic compounds or ester compounds);
[0106] The bladder wall comprises an inner layer and an outer layer, the inner layer is melamine resin, and the outer layer is rubber material;
[0107] The mass ratio of the capsule core, the inner layer and the outer layer is 1:1.2-1.5:0.4-0.5.
[0108] In some other specific embodiments of the present invention, the microcapsule comprises a capsule core and a capsule wall, the capsule core is wrapped in the capsule wall, the capsule core contains an active component, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula:
[0109] Y=0.42X 2 -0.92X+T
[0110] Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1;
[0111] The thickness of the capsule wall is 3.1-5 μm;
[0112] The active component is an inhibitor for inhibiting the release of asphalt smoke (such as aldehyde compounds, ketone compounds, alcohol compounds, phenolic compounds or ester compounds);
[0113] The bladder wall comprises an inner layer and an outer layer, the inner layer is melamine resin, and the outer layer is rubber material;
[0114] The mass ratio of the capsule core, the inner layer and the outer layer is 1:1.7-2:0.6-0.7.
[0115] The present invention also provides a method for preparing microcapsules, the method comprising:
[0116] (1) mixing the active ingredient, emulsifier and water to form an oil-in-water emulsion;
[0117] (2) reacting the oil-in-water emulsion with a resin prepolymer, and then filtering, washing, and drying to obtain a pre-coated material;
[0118] (3) In the presence of a volatile solvent, the rubber material and the pre-coated material are mixed, and then the obtained mixture is mixed with water, and the temperature is raised until the volatile solvent evaporates to obtain microcapsules.
[0119] In step (1), the mixing process can be carried out in a shearing machine, and the operating conditions may include: a rotation speed of 2000-4000 r / min and a time of 20-30 min.
[0120] In step (1), the mass ratio of the active component, the emulsifier and water can be 1: (0.05-0.09): (6-9).
[0121] In some embodiments, the operation process of step (1) is: dissolving the active component in water, then adding the emulsifier, and then performing high-speed shear emulsification at a rotation speed of 2000-4000 r / min.
[0122] In step (2), before the oil-in-water emulsion reacts with the resin prepolymer, the pH value of the oil-in-water emulsion is adjusted to below 5, preferably 2 to 4. The reagent used to adjust the pH value can be a conventional inorganic acid solution, such as dilute hydrochloric acid.
[0123] In step (2), the reaction of the oil-in-water emulsion and the resin prepolymer is carried out under stirring. The stirring speed may be 400-800 r / min, the reaction temperature may be 60-90° C., and the reaction time may be 1-5 h.
[0124] In step (2), the filtration process may be suction filtration.
[0125] In step (2), the washing process may include washing with water and ethanol twice or more respectively.
[0126] In step (2), the drying process can be carried out in an oven, the drying temperature can be 60-90° C., and the drying time can be 5-10 hours.
[0127] In step (2), the resin prepolymer may be one or more of a melamine resin prepolymer, a urea-formaldehyde resin prepolymer and a polymethyl methacrylate prepolymer. Preferably, the resin prepolymer is a melamine resin prepolymer. The preparation method of the melamine resin prepolymer may include: mixing and dissolving melamine and formaldehyde solution with water, adjusting the pH value to 7.5-9.5, and then placing it in a constant temperature water bath at 60-90° C., and reacting for 0.5-3.5 hours under stirring. In the preparation process of the melamine resin prepolymer, the concentration of the formaldehyde solution may be 30-40wt.%. The mass ratio of the amount of melamine, the formaldehyde solution and water may be 1:(2-3):(8-10).
[0128] In step (3), the mass ratio of the rubber material, the volatile solvent and water can be 1:(10-20):(50-150).
[0129] In the method of the present invention, the active component, the resin prepolymer and the rubber material are used in such amounts that the content of the capsule core in the prepared microcapsules is 27-53wt.%, and the content of the capsule wall is 47-73wt.%.
[0130] In the method of the present invention, the active component can be selected from one or any combination of at least two of the aromatic hydrocarbon-rich component, aldehyde compounds, ketone compounds, alcohol compounds, phenolic compounds and ester compounds. Specifically, the aromatic hydrocarbon-rich component, the aldehyde compounds, the ketone compounds, the alcohol compounds, the phenolic compounds and the ester compounds are selected from the same materials as described above.
[0131] In the method of the present invention, the rubber material may be at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
[0132] In the method described in the present invention, the emulsifier can be selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyldimethylhydroxyethylammonium chloride, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and hexadecane polyoxyethylene ether.
[0133] In the method of the present invention, the volatile solvent can be selected from at least one of carbon tetrachloride, dichloromethane and trichloroethylene.
[0134] The invention also provides microcapsules prepared by the method.
[0135] The present invention also provides application of the microcapsule in road asphalt.
[0136] The microcapsules and their preparation methods and applications of the present invention are further described below by way of examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0137] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0138] Example 1
[0139] (1) After adding 1 part by weight of catalytic cracking oil slurry (aromatic content: 50 wt.%) to 9 parts by weight of water at 60° C., 0.05 parts by weight of hexadecyltrimethylammonium bromide was added, and shearing and emulsification were performed at 2000 r / min using a shearing machine for 30 minutes to form an oil-in-water emulsion in the aqueous phase.
[0140] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8.5, and then placed in a constant temperature water bath at 60° C. and stirred at 800 r / min for 0.5 h to obtain a melamine resin prepolymer.
[0141] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 2, and 0.18 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75° C. for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60° C. for 10 hours to obtain a pre-coated material.
[0142] (3) 0.21 parts by weight of chlorinated rubber was dissolved in 1 part by weight of dichloromethane, and 1 part by weight of the pre-coated material was added and stirred thoroughly. The obtained mixture was added to water, stirred at 500 r / min, and the temperature was increased until the solvent evaporated to obtain microcapsules A1, the size of which was 7-9 μm, and its SEM image was as shown in FIG. Figure 1 Through testing, it is known that the content of the capsule core in the microcapsule is 30wt.%, the content of the capsule wall is 70wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 3.1:1.
[0143] The elastic modulus of the microcapsule A1 was measured by a nanoindenter to be 2.4 GPa, and the thickness of the capsule wall of the microcapsule A1 was measured by a scanning electron microscope on a frozen section of the microcapsule to be 3.2 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0144] Example 2
[0145] (1) After adding 1 part by weight of waste lubricating oil (aromatic content of 52 wt.%) to 7 parts by weight of water at 60° C., 0.06 parts by weight of nonylphenol polyoxyethylene ether was added, and shearing and emulsification were performed at 2500 r / min using a shearing machine for 25 minutes to form an oil-in-water emulsion in the aqueous phase.
[0146] (2) 1 part by weight of melamine, 3 parts by weight of a 37 wt.% formaldehyde solution and 10 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 7.5, and then placed in a constant temperature water bath at 80° C. and stirred at 600 r / min for 1 hour to obtain a melamine resin prepolymer.
[0147] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 4, and 0.13 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 600 r / min, and reacted at 70°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 70°C for 8 hours to obtain a pre-coated material.
[0148] (3) Dissolve 0.15 parts by weight of chloroprene rubber in 3 parts by weight of carbon tetrachloride, add 1 part by weight of the pre-coated material, and stir and mix thoroughly. Add the obtained mixture into water, stir at 600 r / min, and increase the temperature until the solvent evaporates to obtain microcapsules A2, the size of which is 4-6 μm. Through detection, it is known that the content of capsule core in the microcapsule is 43wt.%, the content of capsule wall is 57wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 3.4:1.
[0149] The elastic modulus of the microcapsule A2 measured by a nanoindenter is 0.7 GPa, and the thickness of the capsule wall of the microcapsule A2 measured by a scanning electron microscope on a frozen section of the microcapsule is 1.5 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0150] Example 3
[0151] (1) After adding 1 part by weight of furfural extracted oil (aromatic content: 53 wt.%) to 7 parts by weight of water at 60° C., 0.09 parts by weight of octylphenol polyoxyethylene ether was added, and shearing and emulsification were performed at 3000 r / min using a shearing machine for 20 minutes to form an oil-in-water emulsion in the aqueous phase.
[0152] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8, and then placed in a constant temperature water bath at 70° C. and stirred at 500 r / min for 2 h to obtain a melamine resin prepolymer.
[0153] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 3, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 65°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain a pre-coated material.
[0154] (3) 0.2 parts by weight of styrene-butadiene rubber was dissolved in 3 parts by weight of dichloromethane, and 1 part by weight of the pre-coated material was added, and the mixture was stirred thoroughly. The obtained mixture was added into water, stirred at 700 r / min, and the temperature was raised until the solvent evaporated, and microcapsules A3 were obtained, the size of which was 4-6 μm. Through detection, it was found that the content of capsule core in the microcapsule was 43wt.%, the content of capsule wall was 57wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 2.4:1.
[0155] The elastic modulus of the microcapsule A3 measured by a nanoindenter is 0.6 GPa, and the thickness of the capsule wall of the microcapsule A3 measured by a scanning electron microscope on a frozen section of the microcapsule is 1.4 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0156] Example 4
[0157] (1) After adding 1 part by weight of furfural extracted oil (aromatic content: 55 wt.%) to 6 parts by weight of water at 60° C., 0.06 parts by weight of sodium dodecylbenzene sulfonate was added, and shearing and emulsification were performed at 4000 r / min using a shearing machine for 20 minutes to form an oil-in-water emulsion in the aqueous phase.
[0158] (2) 1 part by weight of melamine, 3 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 7.5, and then placed in a constant temperature water bath at 60° C. and stirred at 700 r / min for 2 h to obtain a melamine resin prepolymer.
[0159] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 3, and 0.11 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 60°C for 5 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain a pre-coated material.
[0160] (3) Dissolve 0.16 parts by weight of chlorinated rubber in 1.7 parts by weight of dichloromethane, add 1 part by weight of the pre-coated material, and stir thoroughly. Add the obtained mixture into water, stir at 800 r / min, and increase the temperature until the solvent evaporates, so that the chlorinated rubber gradually forms a film and adheres to the outer wall of the inner wall coating repair material to obtain microcapsules A4, the size of which is 3-5 μm. Through detection, it is known that the content of the capsule core in the microcapsule is 49wt.%, the content of the capsule wall is 51wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 2.7:1.
[0161] The elastic modulus of the microcapsule A4 was measured by a nanoindenter to be 0.5 GPa, and the thickness of the capsule wall of the microcapsule A4 was measured by a scanning electron microscope on a frozen section of the microcapsule to be 0.7 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0162] Example 5
[0163] (1) After adding 1 part by weight of oil extracted from the four-line reduction system (aromatic content of 56 wt.%) to 6 parts by weight of water at 60° C., 0.08 parts by weight of hexadecyltrimethylammonium chloride was added, and shearing and emulsification were performed at 3000 r / min using a shearing machine for 30 minutes to form an oil-in-water emulsion in the aqueous phase.
[0164] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8, and then placed in a constant temperature water bath at 90° C. and stirred at 400 r / min for 3.5 hours to obtain a melamine resin prepolymer.
[0165] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 2, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 800 r / min, and reacted at 90°C for 1 hour. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 9 hours to obtain a pre-coated material.
[0166] (3) Dissolve 0.18 parts by weight of chlorinated rubber in 5 parts by weight of dichloromethane, add 1 part by weight of the pre-coated material, and stir thoroughly. Add the obtained mixture into water, stir at 700 r / min, and increase the temperature until the solvent evaporates, so that the chlorinated rubber gradually forms a film and adheres to the outer wall of the inner wall coating repair material to obtain microcapsule A5, the size of which is 3-6 μm. Through detection, it is known that the content of the capsule core in the microcapsule is 46wt.%, the content of the capsule wall is 54wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 2.5:1.
[0167] The elastic modulus of the microcapsule A5 was measured to be 0.6 GPa by a nanoindenter, and the thickness of the capsule wall of the microcapsule A5 was measured to be 1.0 μm by a scanning electron microscope on a frozen section of the microcapsule, which was consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0168] Example 6
[0169] Microcapsules were prepared according to the method of Example 1, except that urea-formaldehyde resin prepolymer was used instead of melamine resin prepolymer, wherein the preparation process of urea-formaldehyde resin prepolymer was as follows: 1 part by weight of urea, 2 parts by weight of formaldehyde solution with a concentration of 37wt.% and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 9, and then placed in a constant temperature water bath at 60°C, stirred at 800r / min for 0.5h to obtain urea-formaldehyde resin prepolymer. Thus, microcapsules A6 were obtained, and the size of the microcapsules was 6-9μm. Through detection, it was found that the content of the capsule core in the microcapsule was 30wt.%, the content of the capsule wall was 70wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 3.1:1.
[0170] The elastic modulus of the microcapsule A6 was measured to be 2.1 GPa by a nanoindenter, and the thickness of the capsule wall of the microcapsule A6 was measured to be 3.1 μm by a scanning electron microscope on a frozen section of the microcapsule, which was consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0171] Comparative Example 1
[0172] (1) After adding 1 part by weight of catalytic cracking oil slurry (aromatic content: 50 wt.%) to 9 parts by weight of water at 60° C., 0.05 parts by weight of hexadecyltrimethylammonium bromide was added, and shearing and emulsification were performed at 2000 r / min using a shearing machine for 30 minutes to form an oil-in-water emulsion in the aqueous phase.
[0173] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8.5, and then placed in a constant temperature water bath at 60° C. and stirred at 800 r / min for 0.5 h to obtain a melamine resin prepolymer.
[0174] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 2, and 0.18 part by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and dried in an oven at 60°C for 10 hours. The prepared product was used as microcapsule D1, and its size was 5-7 μm.
[0175] The elastic modulus of the microcapsule D1 measured by a nanoindenter is 2.7 GPa, and the thickness of the capsule wall of the microcapsule D1 measured by a scanning electron microscope on a frozen section of the microcapsule is 2.2 μm, which does not conform to the calculation formula Y=0.42X 2 -0.92X+T.
[0176] Comparative Example 2
[0177] (1) After adding 1 part by weight of catalytic cracking oil slurry (aromatic content: 50 wt.%) to 9 parts by weight of water at 60° C., 0.05 parts by weight of hexadecyltrimethylammonium bromide was added, and shearing and emulsification were performed at 2000 r / min using a shearing machine for 30 minutes to form an oil-in-water emulsion in the aqueous phase.
[0178] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8.5, and then placed in a constant temperature water bath at 60° C. and stirred at 800 r / min for 0.5 h to obtain a melamine resin prepolymer.
[0179] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 2, and 0.18 part by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75°C for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 10 hours to obtain a pre-coated material.
[0180] (3) 0.1 parts by weight of chlorinated rubber and 1 part by weight of the pre-coated material are directly added into water, stirred at 500 r / min, and dried to obtain microcapsules D2 having a size of 8-10 μm, wherein the chlorinated rubber in the microcapsule is not wrapped in the outermost layer of the microcapsule in the form of a membrane.
[0181] The elastic modulus of the microcapsule D2 measured by a nanoindenter is 2.6 GPa, and the thickness of the capsule wall of the microcapsule D2 measured by a scanning electron microscope on a frozen section of the microcapsule is 4.1 μm, which does not conform to the calculation formula Y=0.42X 2 -0.92X+T.
[0182] Test Example 1
[0183] The microcapsules prepared in the above Examples 1-6 and Comparative Examples 1-2 were used for testing.
[0184] Donghai No. 70 asphalt was used, and 0.4wt.% of microcapsules were added. Referring to the ductility test method in JTG E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering", the specimen was cut in the middle and placed for 24 hours to test the ductility change before and after, and the healing rate was calculated. The results are shown in Table 1.
[0185] Healing rate = elongation after 24 hours of cutting / elongation before cutting
[0186] Table 1: Ductility test results of asphalt samples
[0187]
[0188] It can be seen from the results in Table 1 that the use of the microcapsules described in the present invention and the selection of a repairing agent for self-repair of pavement cracks as an active component can effectively improve the self-repair efficiency of pavement asphalt materials.
[0189] Example 7
[0190] (1) After adding 1 part by weight of p-methoxybenzaldehyde to 9 parts by weight of water at 60° C., 0.05 parts by weight of hexadecyltrimethylammonium bromide was added, and the mixture was sheared and emulsified at 2000 r / min for 30 minutes to form an oil-in-water emulsion in the aqueous phase.
[0191] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 8 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8.5, and then placed in a constant temperature water bath at 60° C. and stirred at 800 r / min for 0.5 h to obtain a melamine resin prepolymer.
[0192] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 2, and 0.18 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 700 r / min, and reacted at 75° C. for 2 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60° C. for 10 hours to obtain a pre-coated material.
[0193] (3) 0.21 parts by weight of chlorinated rubber was dissolved in 1 part by weight of dichloromethane, and 1 part by weight of the pre-coated material was added, and the mixture was stirred thoroughly. The obtained mixture was added into water, stirred at 500 r / min, and the temperature was raised until the solvent evaporated, and microcapsules A7 were obtained, the size of which was 7-9 μm. Through detection, it was found that the content of capsule core in the microcapsule was 30wt.%, the content of capsule wall was 70wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall was 3.1:1.
[0194] The elastic modulus of the microcapsule A7 measured by a nanoindenter is 2.1 GPa, and the thickness of the capsule wall of the microcapsule A7 measured by a scanning electron microscope on a frozen section of the microcapsule is 3.0 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0195] Example 8
[0196] (1) After adding 1 part by weight of acetophenone to 7 parts by weight of water at 60° C., 0.06 parts by weight of nonylphenol polyoxyethylene ether was added, and the mixture was sheared and emulsified at 2500 r / min for 25 minutes to form an oil-in-water emulsion in the aqueous phase.
[0197] (2) 1 part by weight of melamine, 3 parts by weight of a 37 wt.% formaldehyde solution and 10 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 7.5, and then placed in a constant temperature water bath at 80° C. and stirred at 600 r / min for 1 hour to obtain a melamine resin prepolymer.
[0198] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 4, and 0.13 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 600 r / min, and reacted at 70°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 70°C for 8 hours to obtain a pre-coated material.
[0199] (3) Dissolve 0.15 parts by weight of chloroprene rubber in 3 parts by weight of carbon tetrachloride, add 1 part by weight of the pre-coated material, and stir and mix thoroughly. Add the obtained mixture into water, stir at 600 r / min, and increase the temperature until the solvent evaporates to obtain microcapsules A8, the size of which is 4-6 μm. Through detection, it is known that the content of capsule core in the microcapsule is 43wt.%, the content of capsule wall is 57wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 3.4:1.
[0200] The elastic modulus of the microcapsule A8 was measured by a nanoindenter to be 0.6 GPa, and the thickness of the capsule wall of the microcapsule A8 was measured by a scanning electron microscope on a frozen section of the microcapsule to be 1.4 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0201] Example 9
[0202] (1) After adding 1 part by weight of benzyl alcohol to 7 parts by weight of water at 60° C., 0.09 parts by weight of octylphenol polyoxyethylene ether was added, and shearing and emulsification were performed at 3000 r / min using a shearing machine for 20 minutes to form an oil-in-water emulsion in the water phase.
[0203] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8, and then placed in a constant temperature water bath at 70° C. and stirred at 500 r / min for 2 h to obtain a melamine resin prepolymer.
[0204] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 3, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 65°C for 3 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain a pre-coated material.
[0205] (3) 0.2 parts by weight of styrene-butadiene rubber was dissolved in 3 parts by weight of dichloromethane, and 1 part by weight of the pre-coated material was added, and the mixture was stirred thoroughly. The obtained mixture was added into water, stirred at 700 r / min, and the temperature was raised until the solvent evaporated, and microcapsules A9 were obtained, the size of which was 4-6 μm. Through detection, it was found that the content of capsule core in the microcapsule was 43wt.%, the content of capsule wall was 57wt.%, and the mass ratio of inner layer to outer layer in the capsule wall was 2.4:1.
[0206] The elastic modulus of the microcapsule A9 measured by a nanoindenter is 0.5 GPa, and the thickness of the capsule wall of the microcapsule A9 measured by a scanning electron microscope on a frozen section of the microcapsule is 1.2 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0207] Example 10
[0208] (1) After adding 1 part by weight of 3-propenyl-6-ethoxyphenol to 6 parts by weight of water at 60° C., 0.06 parts by weight of sodium dodecylbenzenesulfonate was added, and shearing and emulsification were performed at 4000 r / min using a shearing machine for 20 minutes to form an oil-in-water emulsion in the aqueous phase.
[0209] (2) 1 part by weight of melamine, 3 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 7.5, and then placed in a constant temperature water bath at 60° C. and stirred at 700 r / min for 2 h to obtain a melamine resin prepolymer.
[0210] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 3, and 0.11 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 500 r / min, and reacted at 60°C for 5 hours. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 90°C for 6 hours to obtain a pre-coated material.
[0211] (3) Dissolve 0.16 parts by weight of chlorinated rubber in 1.7 parts by weight of dichloromethane, add 1 part by weight of the pre-coated material, and stir thoroughly. Add the obtained mixture into water, stir at 800 r / min, increase the temperature until the solvent evaporates, and make the chlorinated rubber gradually form a film and adhere to the outer wall of the inner wall coating repair material to obtain microcapsule A10, the size of which is 3-5 μm. Through detection, it is known that the content of the capsule core in the microcapsule is 49wt.%, the content of the capsule wall is 51wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 2.7:1.
[0212] The elastic modulus of the microcapsule A10 measured by a nanoindenter is 0.4 GPa, and the thickness of the capsule wall of the microcapsule A10 measured by a scanning electron microscope on a frozen section of the microcapsule is 0.8 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0213] Embodiment 11
[0214] (1) After adding 1 part by weight of phenylethyl phenylacetate to 6 parts by weight of water at 60° C., 0.08 parts by weight of hexadecyltrimethylammonium chloride was added, and shearing and emulsification were performed for 30 minutes using a shearing machine at 3000 r / min to form an oil-in-water emulsion in the water phase.
[0215] (2) 1 part by weight of melamine, 2 parts by weight of a 37 wt.% formaldehyde solution and 9 parts by weight of deionized water were fully dissolved in a three-necked flask, the pH value was adjusted to 8, and then placed in a constant temperature water bath at 90° C. and stirred at 400 r / min for 3.5 hours to obtain a melamine resin prepolymer.
[0216] Dilute hydrochloric acid was added dropwise to 1 part by weight of the oil-in-water emulsion to adjust the pH value to 2, and 0.12 parts by weight of the prepared melamine resin prepolymer was slowly added dropwise to the oil-in-water emulsion, stirred at 800 r / min, and reacted at 90°C for 1 hour. After the reaction, the obtained mixed solution was filtered, washed twice with water and ethanol respectively, and placed in an oven at 60°C for 9 hours to obtain a pre-coated material.
[0217] (3) Dissolve 0.18 parts by weight of chlorinated rubber in 5 parts by weight of dichloromethane, add 1 part by weight of the pre-coated material, and stir thoroughly. Add the obtained mixture into water, stir at 700 r / min, and increase the temperature until the solvent evaporates, so that the chlorinated rubber gradually forms a film and adheres to the outer wall of the inner wall coating repair material to obtain microcapsule A11, the size of which is 3-6 μm. Through detection, it is known that the content of the capsule core in the microcapsule is 46wt.%, the content of the capsule wall is 54wt.%, and the mass ratio of the inner layer to the outer layer in the capsule wall is 2.5:1.
[0218] The elastic modulus of the microcapsule A11 was measured by a nanoindenter to be 0.5 GPa, and the thickness of the capsule wall of the microcapsule A11 was measured by a scanning electron microscope on a frozen section of the microcapsule to be 0.9 μm, which is consistent with the calculation formula Y=0.42X 2 -0.92X+T.
[0219] Comparative Example 3
[0220] Microcapsules were prepared according to the method of Example 7, except that in step (1), the amount of water was increased to 15 parts by weight, and the amount of chlorinated rubber was increased to 0.25 parts by weight. Finally, capsules D3 were obtained, the size of which was 6-8 μm.
[0221] The elastic modulus of the microcapsule D3 measured by a nanoindenter is 3.3 GPa, and the thickness of the capsule wall of the microcapsule D3 measured by a scanning electron microscope on a frozen section of the microcapsule is 3.5 μm, which does not conform to the calculation formula Y=0.42X 2 -0.92X+T.
[0222] Comparative Example 4
[0223] Microcapsules were prepared according to the method of Example 7, except that in step (3), the amount of chlorinated rubber was reduced to 0.11 parts by weight, and the amount of melamine resin prepolymer was increased to 0.23 parts by weight, and finally capsule D4 was obtained, the size of which was 5-7 μm.
[0224] The elastic modulus of the microcapsule A6 measured by a nanoindenter is 2.6 GPa, and the thickness of the capsule wall of the microcapsule A6 measured by a scanning electron microscope on a frozen section of the microcapsule is 2.9 μm, which does not conform to the calculation formula Y=0.42X 2 -0.92X+T.
[0225] Test Example 2
[0226] The microcapsules prepared in the above Examples 7-11 and Comparative Examples 3-4 were used for testing.
[0227] Donghai No. 70 asphalt was used, 0.4 wt.% of microcapsules were added, and the asphalt flue gas was enriched under the condition of heating at 163°C for 6 hours. The asphalt flue gas was tested and analyzed by gas chromatography and total hydrocarbon analyzer. The results are shown in Table 2.
[0228] Table 2: Asphalt smoke test results
[0229]
[0230]
[0231] It can be seen from the results in Table 2 that the use of the microcapsules of the present invention and the selection of an inhibitor for inhibiting the release of asphalt smoke as an active component can effectively reduce the emission of asphalt smoke and reduce pollution to the environment.
[0232] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A microcapsule, characterized in that: The microcapsule comprises a capsule core and a capsule wall, wherein the capsule core is wrapped in the capsule wall, the capsule core contains active components, and the elastic modulus of the microcapsule and the thickness of the capsule wall satisfy the following formula: Y = 0.42X 2 - 0.92X + T Wherein, Y is the elastic modulus of the microcapsule, in GPa; X is the thickness of the capsule wall, in μm; T is 1±0.1; The elastic modulus of the microcapsule is obtained by testing the mechanical properties of the microcapsule using a nanoindenter, and the thickness of the capsule wall is obtained by testing the frozen sections of the microcapsule using a scanning electron microscope.
2. The microcapsule according to claim 1, characterized in that Based on the total weight of the microcapsule, the content of the capsule core is 27-53wt.%, and the content of the capsule wall is 47-73wt.%.
3. The microcapsule according to claim 1 or 2, characterized in that The active component is a repairing agent for self-repairing of road cracks and / or an inhibitor for inhibiting the release of asphalt smoke.
4. The microcapsule according to claim 3, characterized in that The repairing agent for self-repair of road cracks is rich in aromatic hydrocarbon components; Preferably, the aromatics-rich component is selected from at least one of catalytic cracking slurry, oil extracted from a four-line reduction reactor, furfural extracted oil and waste lubricating oil; Preferably, the aromatic content of the aromatic-rich component is 45-65 wt.%.
5. The microcapsule according to claim 3, characterized in that The inhibitor for inhibiting the release of asphalt smoke is at least one of aldehyde compounds, ketone compounds, alcohol compounds, phenol compounds and ester compounds; Preferably, the aldehyde compound is selected from aliphatic aldehydes having carbon atoms greater than or equal to 7 and aromatic aldehydes having carbon atoms greater than or equal to 6, more preferably at least one of p-tolualdehyde, decanal, o-carboxybenzaldehyde, p-isopropylbenzaldehyde, cinnamaldehyde, p-hydroxybenzaldehyde, p-methoxybenzaldehyde, 2-methyl-3-(3,4-methylene-dioxyphenyl)propanal, 3,4-methylenedioxybenzaldehyde, 3-(4-isopropylphenyl)-2-methylpropanal, ethyl vanillin, phenylacetaldehyde, anisaldehyde, nonadiene-2,6-aldehyde, 2,6-dimethyl-2,6-octadienal, vanillin, citronellal, neral, hydroxymethylpentylcyclohexene acetal, p-diethylaminobenzaldehyde and undecenal; Preferably, the ketone compound is selected from aliphatic ketones having carbon atoms greater than or equal to 8 and aromatic ketones having carbon atoms greater than or equal to 8, more preferably at least one of 6-methyl-3,5-heptadien-2-one, 2-undecanone, acetophenone, ionone, irone, methylionone, damascenone and dihydrodamascenone; Preferably, the alcohol compound is an alcohol having more than 6 carbon atoms, more preferably at least one of cinnamyl alcohol, menthol, cis-3,7-dimethyl-2,6-octadienol, citronellol, geraniol, myrcenol, 2,6,10-trimethyl-2,6,10-dodecatrien-12-ol, lavandulol, benzylenol, 2-phenylethanol, dihydromyrcenol, tetrahydrogeraniol and nerolidol; Preferably, the phenolic compound is a phenol having 6 or more carbon atoms, more preferably at least one of thymol, ethyl maltol, methyl maltol, 3-propenyl-6-ethoxyphenol and isoeugenol; Preferably, the ester compound is an ester having a carbon number greater than 7, more preferably at least one of methyl salicylate, methyl cinnamate, ethyl cinnamate, ethyl phenylacetate, methyl phenylacetate, geranyl phenylacetate, phenylethyl phenylacetate, isoamyl phenylacetate, benzyl salicylate, p-methylbenzyl acetate, benzyl acetate, isobutyl benzoate, isoamyl salicylate, benzyl cinnamate, phenylethyl cinnamate, linalyl formate, linalyl acetate, linalyl isobutyrate, menthyl acetate, pine acetate and bornyl acetate.
6. The microcapsule according to any one of claims 1 to 5, characterized in that The thickness of the capsule wall is 0.5-5 μm.
7. The microcapsule according to any one of claims 1 to 6, characterized in that The bladder wall comprises an inner layer and an outer layer, the inner layer is a resin, and the outer layer is a rubber material; Preferably, the mass ratio of the inner layer to the outer layer is 2.4-5:
1.
8. The microcapsule according to claim 7, characterized in that The resin is at least one of melamine resin, urea-formaldehyde resin and polymethyl methacrylate, preferably melamine resin.
9. The microcapsule according to claim 7, characterized in that The rubber material is at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
10. The microcapsule according to any one of claims 1 to 9, characterized in that The size of the microcapsule is less than 50 μm, preferably less than 20 μm, and more preferably 3-15 μm.
11. A method for preparing microcapsules, characterized in that: The method includes: (1) Mixing the active ingredient, emulsifier and water to form an oil-in-water emulsion; (2) reacting the oil-in-water emulsion with a resin prepolymer, and then filtering, washing, and drying to obtain a pre-coated material; (3) In the presence of a volatile solvent, the rubber material and the pre-coated material are mixed, and then the obtained mixture is mixed with water, and the temperature is increased until the volatile solvent evaporates to obtain microcapsules.
12. The method according to claim 11, characterized in that In step (1), the mass ratio of the active component, the emulsifier and water is 1:(0.05-0.09):(6-9).
13. The method according to claim 11, characterized in that In step (2), before the oil-in-water emulsion reacts with the resin prepolymer, the pH value of the oil-in-water emulsion is adjusted to below 5, preferably 2-4.
14. The method according to claim 11 or 13, characterized in that In step (2), the resin prepolymer is a melamine resin prepolymer; Preferably, the preparation method of the melamine resin prepolymer comprises: mixing and dissolving melamine and formaldehyde solution with water, adjusting the pH value to 7.5-9.5, and then placing in a constant temperature water bath at 60-90° C., and reacting for 0.5-3.5 hours under stirring; Preferably, the concentration of the formaldehyde solution is 30-40wt.%; Preferably, the mass ratio of the melamine, the formaldehyde solution and the water is 1:(2-3):(8-10).
15. The method according to claim 11, characterized in that In step (3), the mass ratio of the rubber material, the volatile solvent and water is 1:(10-20):(50-150).
16. The method according to any one of claims 11 to 15, characterized in that: The active component is one or any combination of at least two or more of an aromatic hydrocarbon-rich component, an aldehyde compound, a ketone compound, an alcohol compound, a phenol compound and an ester compound.
17. The method according to any one of claims 11 to 16, characterized in that: The rubber material is at least one of chlorinated rubber, styrene-butadiene rubber and chloroprene rubber.
18. The method according to any one of claims 11 to 16, characterized in that: The emulsifier is selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyldimethylhydroxyethylammonium chloride, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether and hexadecane polyoxyethylene ether.
19. The method according to any one of claims 11 to 16, characterized in that: The volatile solvent is selected from at least one of carbon tetrachloride, dichloromethane and trichloroethylene.
20. Microcapsules prepared by the method of any one of claims 11 to 19.
21. Use of the microcapsules according to any one of claims 1 to 10 and 20 in road asphalt.
Citation Information
Patent Citations
Pitch crack self-repair microcapsule containing regenerating agent and preparation method thereof
CN104231642A
Pitch repair agent microcapsule as well as preparation method and application thereof
CN108752952A
Preparation method and application of asphalt concrete self-repairing microcapsule
CN114699996A
Long-acting composite microcapsule asphalt pavement self-repairing agent and application thereof
CN114837033A
Cited By
Microcapsule, preparation method therefor, and use thereof
EP4744766A1